Cartesian dualism and behavior analysis - Pessoti (in memorian), Isaías; Vilares, João Eduardo Cattani (Perspectivas em Análise do Comportamento, 2024)
The incompatibility between radical behaviorism (monistic) and dualism (mind-body) is notorious. The work of René Descartes (1596-1650) – Cartesianism – has been associated with mind-body dualism. This assumption possibly derives from Descartes’ use, throughout his work, of words such as “mind”, “spirit” and “soul”. There are assertions about such incompatibility in Baum’s manual of radical behaviorism (1999/1994). This article presents an analysis of Descartes original writings, presenting results that did not demonstrate a priori the incompatibility pointed out by radical behaviorists, such as Baum. For Descartes, “mind” is not an immaterial entity, or a “homunculus” author of ideas, or an archive of knowledge and experiences, but only the ability to learn to think (behave). The author describes the relationship mind-body as inseparable.